Pijat Tui Na Meningkatkan Berat Badan Balita - Chairunnisa, Rini; Novita, Reni; Siallagan, Dorsinta; Layinah, Ely (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2023)
Nutritional adequacy in toddlers can be met by consuming a variety of foods and a good diet. Nutritional deficiencies lead to growth and development disorders. To overcome to meet the nutritional and nutritional needs of toddlers, one of which is by providing stimulation to increase nerve activity, increase the digestive absorption system, and better absorption of food and can treat nausea, and reduce appetite in children through tui na massage therapy. Tui na is a form of massage therapy and has been used in China for more than 5,000 years. The purpose of this study was to determine the differences in body weight of children under five before and after Tui na massage therapy. The type of research used in this study is Pre Experimental Designs with a one group pretest-posttest design. Where the measurement is taken before doing the treatment (pretest), then the treatment is carried out, namely the action of massage for toddlers tui na and after being given the treatment, it is carried out the measurement again (posttest). Based on the results of the study, there was an average first body weight (pre-test) of 8.3 kg and experienced an increase in body weight after massage with an average of 9.1 kg. The results of the paired-t test obtained the sig level (2-tailed) value of p = 0,000, statistically the value of p = 0,000 <or 0.05, so Ho is rejected and Ha is accepted, which means there is an effect of tui na massage on the increase in body weight of balita in the region. Work at the Suradita Health Center, Tangerang Regency in 2020. Tui na Massage Therapy has an effect on weight gain for toddlers It is hoped that Tui na Massage Therapy can be applied as an innovation to prevent stunting in Suradita Health Centers and throughout Indonesia.